2020
DOI: 10.1016/j.ejphar.2020.173494
|View full text |Cite
|
Sign up to set email alerts
|

Application of methylene blue -vitamin C –N-acetyl cysteine for treatment of critically ill COVID-19 patients, report of a phase-I clinical trial

Abstract: COVID-19 is a global catastrophic event that causes severe acute respiratory syndrome. The mechanism of the disease remains unclear, and hypoxia is one of the main complications. There is no currently approved protocol for treatment. The microbial threat as induced by COVID-19 causes the activation of macrophages to produce a huge amount of inflammatory molecules and nitric oxide (NO). Activation of macrophages population into a pro-inflammatory phenotype induces a self-reinforcing cycle. Oxidative stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
5
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 26 publications
8
99
5
3
Order By: Relevance
“…COVID-19 patients (n = 25) were shown to have a higher MetHb compared to healthy individuals (n = 25) as demonstrated in a cross-sectional study by Alamdari et al [21], supporting the findings reported. However, the cross-sectional study of Soltan et al [19] with a large cohort (534 COVID-19 patients and 114,957 pre-pandemic controls) showed no statistically significant differences in the MetHb values despite the fact that MetHb was an important parameter for the prediction of COVID-19 based on the algorithm the group developed.…”
Section: Is Methb Increased In Covid-19 Patients?supporting
confidence: 78%
See 1 more Smart Citation
“…COVID-19 patients (n = 25) were shown to have a higher MetHb compared to healthy individuals (n = 25) as demonstrated in a cross-sectional study by Alamdari et al [21], supporting the findings reported. However, the cross-sectional study of Soltan et al [19] with a large cohort (534 COVID-19 patients and 114,957 pre-pandemic controls) showed no statistically significant differences in the MetHb values despite the fact that MetHb was an important parameter for the prediction of COVID-19 based on the algorithm the group developed.…”
Section: Is Methb Increased In Covid-19 Patients?supporting
confidence: 78%
“…Based on the inclusion and exclusion criteria, seven duplicates were removed and 187 articles were excluded after abstract review. After the full set of remaining articles was screened, seven reports were finally included in the present study [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The study selection process is shown in Figure 1 a.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing antiviral cytokines, such as interferon (IFN)-α/β [24] Increasing free radical formation to decrease viral yield [25] Attenuating excessive inflammatory response [27] Ameliorating hyperactivation of immune cells by altering energy metabolism [30] Decreased flu or cold symptoms due to treatment with high dose of vitamin C [22,23] Decreased inflammatory mediators/ markers due to the administration of vitamin C in COVID-19 patients [28,29] Table 1. Cont.…”
Section: Consequences Of Deficiency/effects Of Supplementation In Infmentioning
confidence: 99%
“…MeBlu has also been explored in one Phase 1 clinical trial (NCT04370288) for treatment of critically ill COVID-19 patients in Iran as part of a three-drug last therapeutic option add-on cocktail (MeBlu 1 mg/kg, vitamin C 1500 mg/kg, and N-acetyl cysteine 2000 mg/kg) based on the hypothesis that this combination could rebalance NO, methemoglobin, and oxidative stress. Four of the five patients responded well to treatment (Alamdari et al, 2020).…”
Section: Discussionmentioning
confidence: 89%